The Effect of Statins on Ocular Disorders: A Systematic Review of Randomized Controlled Trials - Charoula Lymperopoulou; Stylianos A. Kandarakis; Ismini Tzanaki; Ioanna Mylona; Theodoros Xanthos; Aris P. Agouridis (MDPI AG, 2023)
Aim: Statins have been established in the market not only due to their ability to lower plasma cholesterol levels but also due to their pleiotropic effects. In the literature, there is a controversy regarding the role of statins in ophthalmology. We aimed to systematically address the possible effect of statin therapy on ocular diseases and to identify if there is a beneficial relationship. Methods: We searched PubMed and Cochrane Library databases up to 31 December 2022 for studies evaluating the effect of statins on ocular diseases. We included all relevant Randomized Control Trials (RCTs) that have been conducted in the adult population. PROSPERO registration number: CRD42022364328. Results: Nineteen RCTs were finally considered eligible for this systematic review, with a total of 28,940 participants. Ten studies investigated the role of simvastatin, suggesting a lack of cataractogenic effect and a possible protective role in cataract formation, retinal vascular diseases, and especially diabetic retinopathy, age-related macular disease progression, and non-infectious uveitis. Four studies investigated lovastatin, showing no cataractogenic effect. Three studies examined atorvastatin, revealing conflicting results regarding diabetic retinopathy. Two studies examined rosuvastatin, indicating a possibly harmful effect on lenses and a significant protective effect on retinal microvasculature. Conclusions: Based on our findings, we believe that statins have no cataractogenic effect. There are indications that statins may have a protective role against cataract formation, AMD, diabetic retinopathy progression, and non-infectious uveitis. However, our results were insufficient for any robust conclusion. Future RCTs, with large sample sizes, on the current topic are therefore recommended to provide more solid evidence.